2017
DOI: 10.1016/j.alergo.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The role and choice criteria of antihistamines in allergy management – Expert opinion

Abstract: A b s t r a c tAllergic diseases are the most common chronic conditions lasting throughout the patient's life. They not only cause significant deterioration in the quality of life of patients but also lead to significant absenteeism and reduced productivity, resulting in very high costs for society. Effective and safe treatment of allergic diseases is therefore one of the main challenges for public health and should be carried out by all the specialists in family medicine, internists and paediatricians in coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The current study coincides with [35] who reported that more than half take anti histaminic drugs intravenous. Another study done by [36] reported that majority of study participants take antihistaminic drugs intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…The current study coincides with [35] who reported that more than half take anti histaminic drugs intravenous. Another study done by [36] reported that majority of study participants take antihistaminic drugs intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the vast number of drug‐based treatments available for seasonal allergic rhinoconjunctivitis (ARC), 1 patient dissatisfaction is still an issue. This is partially due to the available medications which do not control the signs and symptoms adequately enough to match the patients' needs, 2‐5 or because the drugs can induce deleterious side effects 6‐9 …”
Section: Introductionmentioning
confidence: 99%
“…Current treatments for allergic conjunctivitis aim to control and relieve the symptoms and include systemic or topical antihistamines, mast cell stabilizers, dual-action agents, anti-inflammatories and corticosteroids [3]. Systemic antihistamines are especially recommended in the presence of other allergic comorbidities [4,5]. Topical antihistamines and mast cell stabilizers are usually well tolerated and reduce symptoms and signs of allergic conjunctivitis, but there are limited data on their long-term efficacy [6].…”
Section: Introductionmentioning
confidence: 99%